Electrically Micro‐Polarized Amorphous Sodo‐Niobate Film Competing with Crystalline Lithium Niobate Second‐Order Optical Response. Issue 13 (7th May 2020) - Karam, Lara; Adamietz, Frédéric; Michau, Dominique; Gonçalves, Claudia; Kang, Myungkoo; Sharma, Rashi; Murugan, Ganapathy Senthil; Cardinal, Thierry; Fargin, Evelyn; Rodriguez, Vincent; Richardson, Kathleen A.; Dussauze, Marc
Abstract: The design of active optical devices integrating second‐order nonlinear (SONL) optical responses typically relies on the use of dielectric crystalline materials such as lithium niobate (LN) or semiconductors such as GaAs. Despite high SONL susceptibilities, these materials present important geometry constrains inherent to their crystalline nature limiting the complexity of the designed photonic systems. Conversely, amorphous materials are versatile optical media compatible with broad platform designs possessing a wide range of optical properties attributable to their composition flexibility. Demonstrated here for the first time in an amorphous inorganic material, a magnitude of SONL optical susceptibility (χ (2) = 29 pm V −1 at 1.06 µm) comparable to that of LN single crystal is reported. By using a thermo‐electrical imprinting process, fine control of the induced uniaxial anisotropy is demonstrated at the micrometer scale. This work paves the way for the future design of integrated nonlinear photonic circuits based on amorphous inorganic materials enabled by the spatially selective and high SONL optical susceptibility of these promising and novel optical materials. Abstract : A second‐order nonlinear susceptibility (χ (2) zzz = 29 pm V ‐1 ) is induced by a thermo‐electrical imprinting treatment in an amorphous thin film. This value is the highest ever reported for an amorphous inorganic material. The induced anisotropy is localized at the micrometer scale, opening the way for new active planar photonic architectures based on amorphous materials.